Tafakkur dalam Kehidupan Persfektif Al-Qur'an dan Hadits - Noff Yanti (Mau'idhoh Hasanah, 2019)
Tafakkur is an important component that must be possessed by every believer, because tafakkur is a reflection of a believer. I can see all the benefits and bad things through it. Thus explained Al-Hasan. With tafakkur, the believer will know the nature and secrets of creating his creations or stories that occur around him. So, in this process, you will also need to know about what is contained in it, as well as the environment. From several suggestions for good recitation from the Qur'an and Hadith that can prove that tafakkur is a very important thing. This is what makes the wisdom expert and the Sufis discuss about taking only to recite about Allah's creation. They understand that by meditating they will find peace, find pleasure and ugliness and know the secret behind the creation of Allah's creation.